Far-field nanoscopy with reversible chemical reactions - Schwering, Michael; Kiel, Alexander; Kurz, Anton; Lymperopoulos, Konstantinos; Sprödefeld, Arnd; Krämer, Roland; Herten, Dirk-Peter (Angewandte Chemie. International edition, 2011)
Revolution in resolution: Abbe's resolution limit has been overcome in fluorescence microscopy by using light-driven processes to switch the emission of fluorophores on and off. Alternatively, chemical reactions can be used, for example the coordination of Cu2+ ions to a fluorescent probe for the stochastic switching between spectroscopic states.
First published: 15 February 2011
Gesehen am 28.10.2022